Audit quality and earnings management: evidence from Portugal - Lopes, Ana Paula (2018)
Accounting manipulation is a current problem, reported in many different contexts. Several audit quality studies indicate that there is a relationship between the quality of the audit and the manipulation of the results. These also show that accruals reduce when the auditor is independent or the audit company is large, and suggest that Big 4 Audit Firms present higher levels of audit quality, when compared with other companies. The aim of this paper is to examine if there is a relationship between the manipulation of results and the quality of the audit, based on the study of the behavior of discretionary accruals in Portuguese non-listed companies. Collected on the SABI (Iberian Balance sheet Analysis System) database, the sample is composed of 4723 companies from 2013 to 2015. The empirical model of this study consists of a multiple linear regression in order to explain the relationship between the discretionary accruals and the firm size, debt, volume business and profitability, based on the Modified Jones Model. The results suggest that there is a relationship between audit quality and earnings manipulation. The level of earnings management is significantly lower among companies contracting a Big 4 audit firm, as compared to companies using a non-Big 4 audit firm.